Model Pengawasan Dewan Perwakilan Rakyat Daerah Terhadap Pemerintah Daerah Dalam Mewujudkan Good Governance (Studi Di Kota Salatiga) Periode 2014-2019 - SUPARNYO, SUPARNYO (2016)
Good local governance can be realized by the government's efforts to accommodate the all aspirations that can be characterized by the existence of policies that pro-people in all aspects becoming the local government's business. In the process of governance, local government will be constantly monitored by various institutions that have authority in the field of supervision, including parliament. To achieve the objective of the policy is strongly influenced by the pattern or model of supervision applied by Parliament. The research method used in this research is descriptive qualitative method. The location researched was the office of DPRD of Parliament inspectorat of Salatiga city of percik salatiga with focus on the model of the control model of Parliament Salatiga city. The impact arising from the process of control by Parliament of Salatiga City is the small possibility the abuse of the policy implementation process the possible the realization of the goal of the policy i.e. good governance and people's welfare. Keyword: Local Government, Regional House Of Representatives, Control, good governance.